The Effect of Ethanol Extract of Malacca Leaves (Phyllanthus emblica) on The Number of Fibroblast Cells in White Rats (Rattus norvegicus) Burns Wound - Ajirni Ajirni; Nuzul Asmilia; Nazaruddin Nazaruddin; Amalia Sutriana; Dian Masyitha; Muhammad Isa (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
Burns are caused by heat exposure, such as fire, radiation, electricity or chemicals that can damage the skin and affect the body's systems. The aim of this study was to find out the effect of the ethanol extract of Malacca leaves (Phyllanthus emblica) on the number of fibroblast cells in white rats (Rattus norvegicus) that have burned. This study used 24 white rats (Rattus norvegicus) were divided into 4 groups that smeared with aquadest as a negative control (P1), 5% ethanol extract gel of Malacca leaves (P2), 10% ethanol extract gel of Malacca leaves (P3), and positive control applied with bioplasenton® gel (P4). The IIA degree burn were created by placing a 2x2 cm hot iron plate on the back of the rat for 5 seconds. The euthanasia performed to all animal and the skin samples were collected after 15 days of treatment. Then histopathological preparations were made using HE staining. The number of fibroblast cells were analyzed by ANOVA test. The average number of white rats (Rattus norvegicus) fibroblast cells that suffered burns P1 (negative control) had a number of 7 ± 1.4 cells/visual. Whereas th e P2 group had a number of 4.2 ± 1.58 cells/visual. This value has a significant difference with the negative control. But the P2 and P3 values (3 ± 1.51 cells/visual) there is no significant different with the P4 value (positive control) with an average number of P4 fibroblast cells were 2 ± 0.4 cells/visual. The results of this study concluded that the ethanol extract of malacca leaves 5% and 10% had an effect againts accelerating burns healing in white rats ( Rattus norvegicus).